Analysis of Production Data from the Krafla Geothermal Field, Iceland - Pruess, K.; Bodvarsson, G. S.; Stefansson, V. (Lawrence Berkeley National Laboratory, 1983)
The Krafla geothermal field in northeastern Iceland consists of several zones, which contain fluids of different composition and thermodynamic state (Stefansson, 1981). In this paper they examine production data from wells which are completed in two-phase zones. Transient changes in flow rate and flowing enthalpy are analyzed to obtain insight into relative (liquid and gas phase) permeabilities, and other reservoir parameters. Numerous studies have shown that predictions of geothermal reservoir behavior are strongly dependent upon the choice of relative permeability functions. There is an extensive literature on gas-oil and oil-water relative permeabilities, but steam-water relative permeabilities which are needed for geothermal reservoir analysis are poorly known. Laboratory experiments by Chen et al. (1978) and Counsil and Ramey (1979) have provided some data which, however, seem to be at variance with relative permeability characteristics deduced from field data by Grant (1977) and Horne and Ramey (1978). The differences may reflect uncertainties in the analysis methods used, or they may reflect ''real'' differences in relative permeability behavior of fractured reservoirs from that of porous medium-type laboratory cores. Recent theoretical work by Menzies (1982) and Gudmundsson et al. (1983) has substantiated the relative permeability characteristics obtained by Horne and Ramey (1978) for Wairakei wells.